Primerjava družbenega in prostorskega razvoja madžarske in italijanske manjšine v Sloveniji, na Hrvaškem in v Srbiji v obdobju po razpadu Jugoslavije - Klemenčič, Matjaž (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The Hungarian and Italian minorities, populating territories in Slovenia, Croatia and Serbia, have in the 20th century undergone major demographic, spatial, political and socioeconomic changes. A century ago, both the communities were still quite numerous (in 1910 there were about 300.000 Italians and over 500.000 Hungarinas) and - regarding their political status -dominant in Austro-Hungary (Hungarians) or Italy (Italians) in the period between the two world wars. Changes of political borders, as well as of legal and actual status caused large oscillations in the numbers of members of the two communities. The cooperation of Italy and Hungary on the side of occupation forces during the WWII brought about mass migrations of mainly Italian (and of course German) population after the war. These emigrations were due to fear, strong Italian propaganda (optants), unfavourable economic conditions, and partly also due to persecution (Esuli). The present territory of settlement of the Italian minority includes coastal settlements in Slovenia(about 3.000 members), in Croatia (about 21.000 members); according tostatistical data, about 25.000 persons altogether. The Hungarian territory of settlement is much larger and much stronger populationwise. It includes a narrow eastern border stretch in Slovenia (8.000 members), individual settlements in Croatia, (together 22.000), and the most extensive part in Vojvodina, mainly in the northern part of Bačka (today about 285.000). There are about 315.000 Hungarians in total, populating the extensive and mostly rural territory of the Pannonian plain. Hungarian community in Croatia and Vovodina saw a substantial decrease in numbers due to forced migrations, civilvictims and refugees in the areas of conflicts and forced mobilizations. According to some estimations the number of Hungarian population has decreasedby at least 30.000 persons. Both the minorities already had differentlegal and actual statuses in individual republics of the former Yugoslavia. They today enjoy by far the most favourable status in Slovenia.
Keywords: Slovenia; Slovenija; Croatia; Hrvaška; Srbija; Serbia; politične spremembe; demografske spremembe; družbene spremembe; etnični odnosi; narodne manjšine; Madžari; Italijani